Proceedings of the 56th Annual Meeting of the Association for Computational Linguistics (Volume 2: Short Papers) 2018
DOI: 10.18653/v1/p18-2057
|View full text |Cite
|
Sign up to set email alerts
|

Hearst Patterns Revisited: Automatic Hypernym Detection from Large Text Corpora

Abstract: Methods for unsupervised hypernym detection may broadly be categorized according to two paradigms: pattern-based and distributional methods. In this paper, we study the performance of both approaches on several hypernymy tasks and find that simple pattern-based methods consistently outperform distributional methods on common benchmark datasets. Our results show that pattern-based models provide important contextual constraints which are not yet captured in distributional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 19 publications
0
110
0
Order By: Relevance
“…To evaluate the efficacy of our method, we evaluate on several commonly-used hypernymy benchmarks (as described in (Roller et al, 2018)) as well as in a reconstruction setting (as described in (Nickel and Kiela, 2017)). Following Roller et al (2018), we compare to the following methods for unsupervised hypernymy detection:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the efficacy of our method, we evaluate on several commonly-used hypernymy benchmarks (as described in (Roller et al, 2018)) as well as in a reconstruction setting (as described in (Nickel and Kiela, 2017)). Following Roller et al (2018), we compare to the following methods for unsupervised hypernymy detection:…”
Section: Methodsmentioning
confidence: 99%
“…Our own experiments, and those of Seitner et al (2016), demonstrate that this approach can be scaled to large corpora such as COM-MONCRAWL. 1 As Roller et al (2018) showed, pattern matches also provide important contextual constraints which boost signal compared to methods based on the Distributional Inclusion Hypothesis.…”
Section: Hearst Graphmentioning
confidence: 99%
See 1 more Smart Citation
“…We remark that the above two approaches both yield contextual units with granularity more coarse than the Simplest, while one can also dene context granularity that is ner than the simplest. For instance, using explicit network structure, meta-graph [32], a denition of a ner contextual unit in the DBLP network can be two papers wrien by the same author. Under this denition, only two keywords simultaneously tagged to an authors' two papers are considered linked to a common contextual unit.…”
Section: Exploiting Context Granularitymentioning
confidence: 99%
“…A substantial number of methods have been proposed to extend the original six Hearst patterns [11,17,57]. It has been shown that Hearst pattern based methods tend to achieve high precision with compromised recall [22,32,53]. Attempts have also been made to further improve the recall [1,24,47].…”
Section: Case Study: Taxonomy Constructionmentioning
confidence: 99%